Pengaruh Penanaman Nilai Budaya Religius dan Lingkungan Sekolah Terhadap Pembentukan Karakter Siswa di SMP Hamalatul Quran Ringinagung Kediri - Kamilah, Aisyatul; Rodiyah, Siti Kholidatur; Chumairoh, Nailul Ulah Al (YASIN, 2025)
Rapid technological changes have both pros and cons, especially for children. Education that emphasizes positive and negative values is crucial for character development in a global society. Through religious education, the ideals of divinity and humanism in Islam shape students' character. This study examines how Islamic cultural values and the educational environment shape student character at SMP Hamalatul Quran Ringinagung Kediri. Data were obtained through surveys, observations, and documentation. Most questionnaire scores fell within the upper range, peaking at 115-116. Validity and reliability tests verified the research instrument. Data were normally distributed, and the regression type was free from multicollinearity and heteroskedasticity. Multiple linear regression analysis revealed that religious cultural values (X1) did not have a significant impact on student character (Y), whereas the school environment had a positive and substantial effect on character education (Y). The coefficient of determination (R²) of 0.295 indicates that religious cultural values and the school environment explain 30% of the variability in student character, although other variables also play a role. The F test revealed that both independent factors significantly affect the dependent variable. This study shows that religious cultural values and the educational environment significantly influence student character. Promoting religious principles in the curriculum, school activities, and a supportive atmosphere can help students develop integrity and morality.